Bacteria Elimination of Xanthomonas axonopodis pv. glycine and Improvement of Viability of Soybean Seeds Through a Combination of Temperature and Duration of Dry Heat Treatment - Aprilia Diandra Savitri; Imelda Milaros; Irene Patria Hannyvone; Evan Purnama Ramdan (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Soybean is the main food crop in Indonesia, besides rice and corn, and its need continues to increase. X. axonopodis pv. glycine (Xag) is a pathogen that causes bacterial pustule disease in soybeans, which can cause soybean productivity to decrease by 57.61%. Xag is also a seed-borne pathogen that spreads through seeds, reaching 8%. Therefore, this study aims to determine the optimum combination of dry heat treatment techniques to eliminate Xag and increase seed viability and vigor. The study was arranged in a randomized complete factorial design consisting of 2 factors: the temperature factor of control, 25 and 45°C, and the duration factor of 6, 12, and 18 hours. Soybean seeds inoculated with Xag were then given a dry heat treatment (DHT) treatment of 100 seeds each. Then, the population of Xag bacteria, germination, vigor index, and seed viability were calculated. The results showed that DHT with a temperature of 45 °C was the best in suppressing the Xag population but reduced soybean seed viability. Therefore, the optimal combination of DHT to eliminate and maintain seed viability is at 25 °C for 12 hours.